Chiral plasmonics - Hentschel, Mario; Duan, Xiaoyang; Liu, Na (Science advances, 2017)
We present a comprehensive overview of chirality and its optical manifestation in plasmonic nanosystems and nanostructures. We discuss top-down fabricated structures that range from solid metallic nanostructures to groupings of metallic nanoparticles arranged in three dimensions. We also present the large variety of bottom-up synthesized structures. Using DNA, peptides, or other scaffolds, complex nanoparticle arrangements of up to hundreds of individual nanoparticles have been realized. Beyond this static picture, we also give an overview of recent demonstrations of active chiral plasmonic systems, where the chiral optical response can be controlled by an external stimulus. We discuss the prospect of using the unique properties of complex chiral plasmonic systems for enantiomeric sensing schemes.
Gesehen am 08.05.2018